2019
DOI: 10.2105/ajph.2019.305202
|View full text |Cite
|
Sign up to set email alerts
|

Relay: A Peer-Delivered Emergency Department–Based Response to Nonfatal Opioid Overdose

Abstract: Relay, a peer-delivered response to nonfatal opioid overdoses, provides overdose prevention education, naloxone, support, and linkage to care to opioid overdose survivors for 90 days after an overdose event. From June 2017 to December 2018, Relay operated in seven New York City emergency departments and enrolled 649 of the 876 eligible individuals seen (74%). Preliminary data show high engagement, primarily among individuals not touched by harm reduction or naloxone distribution networks. Relay is a novel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 5 publications
0
24
2
Order By: Relevance
“…A study of 1329 emergency department peer coaching contacts in Rhode Island demonstrated high rates of patients receiving naloxone training by peer recovery coaches (88.7%) and agreeing to continue contact with a peer recovery coach (86.8%) [ 110 •]. Welch et al demonstrated a 74% enrollment rate ( N =876) in a program linking peer recovery support to overdose survivors for 90 days [ 111 ]. A retrospective study analyzing 555 patients admitted to an ED for overdose or who the ED provider documented as having opioid misuse/opioid use disorder reported high rates of peer recovery coach consultation (85.5%) and distribution of take-home naloxone (95.2%) [ 112 ].…”
Section: Opportunities For Interventionmentioning
confidence: 99%
“…A study of 1329 emergency department peer coaching contacts in Rhode Island demonstrated high rates of patients receiving naloxone training by peer recovery coaches (88.7%) and agreeing to continue contact with a peer recovery coach (86.8%) [ 110 •]. Welch et al demonstrated a 74% enrollment rate ( N =876) in a program linking peer recovery support to overdose survivors for 90 days [ 111 ]. A retrospective study analyzing 555 patients admitted to an ED for overdose or who the ED provider documented as having opioid misuse/opioid use disorder reported high rates of peer recovery coach consultation (85.5%) and distribution of take-home naloxone (95.2%) [ 112 ].…”
Section: Opportunities For Interventionmentioning
confidence: 99%
“…Pilot study participants expressed feeling positively about peer workers, both for the substance use intervention received at baseline and when asked about a hypothetical housing peer navigator intervention. There is increasing interest in use of professional peer‐based interventions in EDs 37–39 and other health care settings, 40,41 though effectiveness research is still limited. Peer‐delivered interventions may hold particular promise for highly stigmatized conditions such as substance use and homelessness and should be studied in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a patient is prescribed an opioid, the electronic health system could trigger a reflex order for naloxone to the patient’s preferred pharmacy. As another example, the Mount Sinai emergency department started a collaboration in early 2020 that connects participants who have had a near fatal overdose to peer “wellness advocates” who are deployed to the ED to offer overdose education, ( Welch et al, 2019 ), naloxone, linkage to care (including to the REACH Program) and supportive follow-up up for 90 days.…”
Section: Discussionmentioning
confidence: 99%